EVALUASI SISTEM AKUNTANSI PENGELUARAN KAS KECIL PADA PT. VARIA USAHA BETON - Iieva Suryananingtys; R. Muh. Syah. Arief Atmaja Wijaya (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
The purpose of this study are to comprehend the design of the PT Varia Usaha Beton petty cash expenditure accounting system and examine the validity of Mulyadi's (2016) evaluation of the system. In this study, only qualitative data were gathered. This study employed a descriptive method of inquiry. The study's conclusions demonstrate that PT Varia Usaha Beton's petty cash expenditure accounting system agrees with Mulyadi's (2016) evaluation. There are, however, a number of items that are still out of compliance with the aspects introduced at PT Varia Usaha Beton, including documentation, records, and internal control.